Comparison of glucose metabolism and anthropometry in women with previous gestational diabetes treated with metformin vs. insulin: 9-year follow-up of two randomized trials - Huhtala Mikael; Nikkinen Hilkka; Paavilainen Elisa; Niinikoski Harri; Vaarasmaki Marja; Loo Britt-Marie; Rönnemaa Tapani; Tertti Kristiina (WILEY, 2022)
Introduction: The main aim was to study whether the long-term incidences of type 2 diabetes, pre-diabetes and metabolic syndrome differed between women who were treated with metformin or insulin for gestational diabetes.
Material and methods: This 9-year follow-up study of two open-label randomized trials compares metformin and insulin treatments of gestational diabetes. In all, 165 women, 88 previously treated with insulin and 77 treated with metformin in the index pregnancy, were included in the analyses. An oral glucose tolerance test was performed, and measures of anthropometry, glucose metabolism, serum lipids and inflammatory markers were compared between the treatment groups. Disorders of glucose metabolism (pre-diabetes and type 2 diabetes) at the 9-year follow-up was the primary outcome of this study. This study was registered at ClinicalTrials.gov: NCT02417090.
Results: The incidences of pre-diabetes and type 2 diabetes (40.3% vs. 46.6%, odds ratio [OR] 0.77, 95% CI 0.40-1.50, p = 0.51), type 2 diabetes (14.3% vs. 15.9%, OR 0.88, 95% CI 0.34-2.26, p = 0.94), pre-diabetes (26.0% vs. 30.7%, OR 0.79, 95% CI 0.38-1.65, p = 0.62), and metabolic syndrome (45.9% vs. 55.2%, OR 0.69, 95% CI 0.35-1.35, p = 0.31) were comparable between the metformin and insulin groups. Moreover, there were no evident differences in the individual measures of anthropometry, glucose metabolism including HOMA-insulin resistance, serum lipids or inflammatory markers between the two treatment groups.
Conclusions: Treatment of gestational diabetes with metformin vs. insulin during pregnancy is unlikely to have diverging long-term effects on maternal anthropometry, glucose metabolism or serum lipids. From this perspective, both treatments may be considered in gestational diabetes.